Genetic analyses of wheat and molecular marker-assisted breeding. Conditional QTL analysis and MAS / Volume 2, (2015) - Tian, Jichun; Chen, Jiansheng; Chen, Guangfeng; Wu, Peng; Zhang, Han; Zhao, Yong
No abstract available